Pengaruh Konten Akun Instagram @Urbansneakersociety Terhadap Minat Beli Sepatu pada Mahasiswa FKI UMS - Pradwita, Ade Yogantara; Santoso, Budi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to analyze the effect of @Urbansneakersociety Instagram Account Content on interest in buying shoes for Fki Ums students. This research is a type of quantitative research. The independent variable (X) in this study is the account content on Instagram @urbansneakersociety and for the dependent variable (Y) is the interest in buying shoes for FKI UMS students. The population in this study are followers of the @urbansneakersociety Instagram account with other criteria, namely 18-25 years old and are FKI UMS students. This type of data collection in this study uses non-propability sampling with purposive sampling technique. The number of samples in this study amounted to 97 people. The instrument in this study used a questionnaire media. The scale used in this data collection process uses a Likert Scale. The data analysis technique of this research is the research instrument test, classical assumption test and normality test, regression test, model feasibility test (Goodness of Fit). From the results of the study, it can be concluded that the Instagram content (X) @urbansneakersociety has an effect on the variable Purchase Interest (Y) shoes on FKI UMS students.